Why We Worry - Paulsen, Roland (Taylor & Francis, 2024)
Something must have changed in society. We weren’t always this worried. Not always caught up in disastrous scenarios in our minds. What is this nagging voice in our head? Why won’t it stop, and why are we so fixated on it? In Why We Worry, Roland Paulsen paints a broad picture of the cultural variations and historical evolution of anxiety. Through this lens, he invites readers to explore the paradox of how material wealth has enriched our lives in every aspect except one: our mental well-being. This book offers empirically grounded insights into the sociological underpinnings of issues relating to worry. As such, it is suitable for undergraduate students in psychology, sociology, and medicine – and anyone who has ever been trapped in rumination.